(untitled) (Anwer Khan Modern Medical College Journal, 2018)
Crohn’s disease is an uncommon disease in Bangladesh. Recently its prevalence is increasing. In the era of tuberculosis, it is sometimes difficult to diagnose in this subcontinent. Mrs. Bilkis Begum 50 years old housewife presented with loose motion with abdominal pain. She had significant weight loss. She was ill looking and anemic. Colonoscopy reveals multiple longitudinal ulcers in the descending colon. Biopsy finding revealed large number of granuloma with aggregates of epithelioid cells, histocytes and few giant cells. No caseation was found. In this scenario anti TB was started and condition of the patient was improved. She has gained her weight. After 6 month of anti Tb therapy repeat colonoscopy was done and revealed multiple healed longitudinal scar marks in the colon. In 15th February 2018 she presented with previous complain. During this time her stool for calprotectin is high. Colonoscopy shows multiple longitudinal ulcers in the sigmoid colon and biopsy shows epithelioid cells and granulation. Now she was diagnosed as a case of crohn’s colitis. Induction of therapy was started with prednisolone along with mesalamine. Condition of the patient improved. Anwer Khan Modern Medical College Journal Vol. 9, No. 2: Jul 2018, P 154-157